2014
DOI: 10.1080/02640414.2014.949826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Actical equations and thresholds to predict physical activity intensity in young children

Abstract: This version is available at https://strathprints.strath.ac.uk/52800/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Accelerometer measurements had previously been validated in healthy children aged 7 to 18 years . Data were collected with a 15‐second epoch interval . Valid measurements required a wear time of at least 500 min/day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerometer measurements had previously been validated in healthy children aged 7 to 18 years . Data were collected with a 15‐second epoch interval . Valid measurements required a wear time of at least 500 min/day.…”
Section: Methodsmentioning
confidence: 99%
“…22 Data were collected with a 15-second epoch interval. 23 Valid measurements required a wear time of at least 500 min/day. When data showed 60 minutes of consecutive zeros on the readout, these data were coded as non-wear time and excluded from the analyses.…”
Section: Physical Activitymentioning
confidence: 99%
“…Sedentary behavior was defined using a cut point of ≤ 25 counts per 15 seconds for the ActiGraph (Janssen et al, 2013b). For the Actical, sedentary behavior was classified using a cut point of ≤ 6 counts per 15 seconds (Janssen et al, 2015). Standing still was calculated by summing up all epochs classified by the activPAL as 15 seconds of standing (excluding stepping).…”
Section: Methodological Decisions When Measuring Sedentary Behavior Amentioning
confidence: 99%
“…In toddlers, preschoolaged children, and school-aged children the ActiGraph ≤ 100 counts per minute cut point appeared most accurate when estimating time spent in sedentary behaviors (Janssen et al, 2012;Trost, Fees, Haar, Murray, & Crowe, 2012;Trost, Loprinzi, Moore, & Pfeiffer, 2011). For the Actical, only one study examined the accuracy of several sedentary behavior cut points in preschool-aged children and found that a cut point of ≤ 6 counts per 15 seconds provided the most accurate estimates (Janssen et al, 2015).…”
Section: Epochs and Cut Pointsmentioning
confidence: 99%
“…by stratifying for quartiles of MVPA). To determine the range of sedentary behaviour cut-points considered valid for each activity monitor, we consulted relevant studies and reviews for the most common devices such as the ActiGraph (30)(31)(32)(33) or Actical (11,31,(34)(35)(36) or examined supporting evidence cited in each study. Items were coded as 'present' (1) or 'absent/unclear' (0), and low ROB was classified as the presence of ≥3/4 items.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%